Features of thermal conditionss of the nonlinear surge arrester at low electric power quality - Шевченко, Сергій Юрійович (Eastern-European Journal of Enterprise Technologies, 2015)
The mathematical model for calculating thermal conditions of nonlinear surge arresters based on experimental research of the current-voltage characteristics in the area of leakage currents was improved in the paper. Improvement of the mathematical model for determining the power, dissipated by SA in the area of leakage currents of CVC will allow to consider both conditions of SA, namely when it is an insulator and when it becomes a conductor, and develop a method for evaluating the SA ability to maintain thermal balance throughout the working life. This method is necessary for the correct SA selection of in networks with low electric power quality and calculation of SA operating conditions under peak working voltage of the network. The results show the presence of the electric power quality influence on the SA thermal conditions. At the SA selection stage, calculation according to the proposed mathematical model allows to determine required bandwidth, which greatly increases the reliability of power supply to electric power consumers. Using the mathematical model, SA manufacturers will be able to produce high-performance devices that will expand their use in networks with low electric power quality.